Isolation Transformer Based Very Low Frequency Antenna with Enhanced Radiation Characteristics - Jingqi Wu; Zilun Zeng; Liwei Wang; Jianchun Xu; Ke Bi (Advanced Science)
Abstract Very low frequency electromagnetic waves adeptly propagate in harsh cross‐medium environments, surmounting the rapid attenuation that impedes high‐frequency counterparts. Traditional low frequency antennas, however, encounter challenges concerning size, efficiency, and power. Here, an isolation transformer based very low frequency loop antenna with compact size and well impedance matching is proposed to enhance radiation characteristics for long‐distance communication. By utilizing the high magnetic permeability amorphous/nanocrystalline alloy Fe73.5Cu1Nb3B9Si13.5, the isolation transformer enables efficient and stable high‐current input. This design surpasses the current limitation of the conventional loop antennas, thereby improving its electromagnetic performance. Consequently, the radiation intensity of proposed antenna can be effectively increased over 30 times compared to traditional loop antennas. According to the experimental measurements, the transmission distance is over 340 m at 15 kHz using a single proposed antenna with a diameter of 2 m. Its robust performance, such as high radiation efficiency, low power consumption, and long‐distance transmission capacity, suggests significant potential for applications in underground communications and underwater information transmission.